A comparison of the efficacy and duration of action of topically applied proxymetacaine using a novel ophthalmic delivery system versus eye drops in healthy young volunteers. Issue 11 (November 1993) - Lawrenson, J G; Edgar, D F; Gudgeon, A C; Burns, J M; Geraint, M; Barnard, N A
Abstract : A novel ophthalmic drug delivery system (NODS) has been developed to give precise and controlled delivery of a drug to the eye. The drug is incorporated into a polyvinyl alcohol flag attached to a carrier. When applied to the eye the flag detaches and gradually dissolves, releasing the drug. We investigated corneal anaesthesia produced by different concentrations of proxymetacaine NODS, and conventional eye drops. Subjects consisted of 28 normal males (mean age 25.3 (SD 3.9) years). Corneal touch sensitivity was measured with a biomicroscope mounted Cochet-Bonnet aesthesiometer. Each subject attended for two visits separated by 7 days. On each visit each eye randomly received one of four proxymetacaine preparations: 44 micrograms, 74 micrograms, 124 micrograms NODS, or 35 microliters of 0.5% proxymetacaine drops (175 micrograms). Corneal touch sensitivity was measured before, and at 1, 2, 5, 10, 15, 20, 30, 45, and 60 minutes following instillation. Complete anesthesia was achieved in the majority of subjects within 1 minute of instillation. The lowest NODS dose (44 micrograms) produced longer lasting anaesthesia than the 35 microliters drop (175 micrograms) (p < 0.05). Higher NODS doses produced a correspondingly greater increase in the duration of anaesthesia. The greater bioavailability achieved by this vehicle allows much lower drug concentrations to be used, reducing the likelihood of systemic adverse reactions.